2015
DOI: 10.1088/1367-2630/17/6/063028
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds numbers and the elliptic approximation near the ultimate state of turbulent Rayleigh–Bénard convection

Abstract: We report results of Reynolds-number measurements, based on multi-point temperature measurements and the elliptic approximation (EA) of He and Zhang (2006 Phys. Rev. E 73 055303), Zhao and He (2009 Phys. Rev. E 79 046316) for turbulent Rayleigh-Bénard convection (RBC) over the Rayleigh-number range Ra 10 2 1 0 11 14≲ ≲ × and for a Prandtl number Pr ≃ 0.8. The sample was a right-circular cylinder with the diameter D and the height L both equal to 112 cm. The Reynolds numbers Re U and Re V were obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 69 publications
18
30
1
Order By: Relevance
“…We also present new measurements of N u which are for the same sample as that used for the study of the azimuthal diffusion. They, as well as Re V measurements reported before (He et al 2015) for a different sample with Γ = 1.00, show the ultimate-state transition and all three physical properties yield consistent results for Ra * 1 and Re * 2 as shown below in Fig. 4.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also present new measurements of N u which are for the same sample as that used for the study of the azimuthal diffusion. They, as well as Re V measurements reported before (He et al 2015) for a different sample with Γ = 1.00, show the ultimate-state transition and all three physical properties yield consistent results for Ra * 1 and Re * 2 as shown below in Fig. 4.…”
Section: Introductionsupporting
confidence: 84%
“…The results of Chavanne et al (1997), Chavanne et al (2001), and Roche et al (2010) (the "Grenoble" data, obtained with fluid helium at a temperature of about 5 Kelvin and a pressure of about 2 bars) found transitions in the Ra range from 10 11 to 10 12 , which in our view (but not that of the authors) is too low to correspond to a BL shear instability although the data clearly show a sharp and continuous transition which, we believe, is of unknown origin (see Ahlers et al (2012b)). Measurements of N u and of the Reynolds number Re V = V L/ν (V is the root-mean-square fluctuation velocity) made with compressed sulfur hexafluoride (SF 6 ) at ambient temperatures and pressures up to 19 bars also found a transition ; Ahlers et al (2012b); He et al (2012aHe et al ( , 2015, the "Göttingen" data], but at Ra * ≃ 10 14 in agreement with the theoretical estimate of Grossmann & Lohse (2002).…”
Section: Introductionsupporting
confidence: 63%
“…At the Max Planck Institute for Dynamics and Self-Organization and the University of California, Santa Barbara, He et al (2012bHe et al ( , 2014He et al ( , 2015 extensively tested the validity of the EA model in turbulent RBC, where Taylor's frozen-flow hypothesis is not valid because of large fluctuations (Lohse & Xia 2010). Their experimental results verify that the temperature correlation contours present similar elliptic shapes and the EA model leads to the collapse of all space-time correlations on the normalized space and time separations.…”
Section: Rayleigh-bénard Convectionmentioning
confidence: 95%
“…We wish to scale the spectra so that they become equal to the analogously scaled spatial spectra within the accuracy of the elliptic approximation of He & Zhang (2006). This is achieved by scaling time by a characteristic time scale τ 0 (see § 5.6 below), which is defined by (5.2) and related to the curvature of the autocorrelation function (3.11) at τ = 0 (He et al 2014(He et al , 2015. This time scale plays a role in the time domain that is analogous to that of the Taylor microscale λ 0 in the spatial domain.…”
Section: A Spatially Uniform Fluctuating Modementioning
confidence: 99%
“…The characteristic time τ 0 plays a role in the time domain that is analogous to that of the Taylor microscale (see e.g. Pope 2000) in the spatial domain (He et al 2014(He et al , 2015. On the basis of the elliptic approximation (EA) of He & Zhang (2006), it can be shown that there is a space-time equivalence when time is scaled with τ 0 and space is scaled with λ 0 , where λ 0 is obtained from a Taylor series expansion, analogous to (5.2), of the spatial autocorrelation function C(z) (z is the spatial displacement; see e.g.…”
Section: The Power Spectramentioning
confidence: 99%